The Relationship Between Family Support, Drug Side Effects, Patient Attitudes and Tuberculosis Treatment Compliance at Dr. R. Soeprapto Cepu Hospital - Safitri, Soffia Narulita; Setiyadi, Noor Alis (Universitas Tribhuwana Tunggadewi, 2025)
This study aims to determine the relationship between family support, drug side effects, knowledge, and patient attitudes with tuberculosis treatment compliance at Dr. R. Soeprapto Cepu Hospital. The research employs a descriptive quantitative design using a cross-sectional method. A total of 165 respondents were selected through purposive sampling based on specific inclusion criteria. Data collection was carried out using structured questionnaires, and the results were analyzed using the Chi-Square statistical test. The findings demonstrated a substantial correlation between family support (p = 0.003), drug side effects (p = 0.015), patient attitude (p = 0.001) and treatment adherence. However, knowledge did not show a significant relationship with adherence (p = 0.433). These results indicate that although knowledge is an essential factor in health behavior, it may not directly influence a patient's commitment to completing tuberculosis treatment. In conclusion, family support, medication side effects, and patient attitudes play a crucial role in improving tuberculosis treatment compliance. Healthcare providers should focus on strengthening family involvement, managing side effects effectively, and fostering positive attitudes in patients to enhance adherence rates. Further research is recommended to explore other potential factors affecting compliance, such as socioeconomic status, healthcare accessibility, and psychological aspects.